Dampak Strategi Pembelajaran Aktif terhadap Pembelajaran Servis Bawah dan Penerimaan Servis dalam Bola Voli bagi Siswa Perempuan Rouaa Abdullah Sakhi - Rouaa Abdullah Sakhi (Indonesian Journal of Physical Education and Sport Science, 2026)
Studi purpose. The study seeks to examine the impact of the application of the active learning strategies in teaching the underhand serve and the serve-receiving skills in volleyball to female students. Materials and methods. The research design used was an experimental research design with two equal groups. The sample was composed of 24 students in the 5th grade of Al-Hariri high school of distinguished students in the 2023-2024 academic year, and six equal groups: experimental group and a control group. Tests were done on the variables used in the research using instruments and devices. Ten fifth-grade female students were selected as a pilot study. Pre tests to test technical performance were done in the under hand serve and serve-receiving skills which are part of the first-semester curriculum. The experimental group was exposed to an eight-week active learning program of two learning units (out of the four). There were post-tests that followed the intervention. Results. The analysis of the data collected statistically indicated that the active learning strategy had a significant impact on enhancing the skills of students in the area of underhand serve and serve-receiving in volleyball. Conclusions. Active learning is a powerful approach to the development of volleyball skills, involvement of students, and their motivation. In the study, the adoption of active learning approach in teaching volleyball and sports skills is suggested.